2003
DOI: 10.1001/archneur.60.10.1439
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cognitive Impairment Following Laterothalamic Infarcts

Abstract: Our observations show that while learning, naming, and gnosic difficulties fit with the classical verbal/nonverbal dichotomy (left and right hemisphere, respectively), executive dysfunctions, including verbal fluency tasks, were more dominant after right thalamic infarcts. Although the observed deficits appeared to be less severe than those generally found with dorsomedial and polar thalamic strokes, the dominance of executive dysfunction suggests that ventrolateral thalamic lesions may disrupt frontothalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 28 publications
3
24
2
1
Order By: Relevance
“…The stroke mechanisms and main clinical features of these infarcts corresponded to patterns described previously, [3][4][5][6]9,16,17 except for paramedian infarcts. After lesions in this territory, memory impairment in our study was less frequent than reported previously.…”
Section: Classical Territoriessupporting
confidence: 68%
“…The stroke mechanisms and main clinical features of these infarcts corresponded to patterns described previously, [3][4][5][6]9,16,17 except for paramedian infarcts. After lesions in this territory, memory impairment in our study was less frequent than reported previously.…”
Section: Classical Territoriessupporting
confidence: 68%
“…Decreased activity in occipital and occipitotemporal cortices may impact visual perception, especially perception related to form [7,46,55] and object recognition [12,19,47]. Decreased processing efficiency in the thalamus can have additional consequences, for it relays almost all incoming sensory information and has been implicated in cognition [3,74], consciousness [29,34], attention [74] and motor integration [23,30]. While these declines may be representative of decreased efficiency or processing specificity, our participants do not show adverse behavioral effects.…”
Section: Resting State Longitudinal Changesmentioning
confidence: 73%
“…The image data were analyzed using Statistical Parametric Mapping (SPM2; Wellcome Department of Cognitive Neurology, London, England), where voxel by voxel comparisons determined significant changes in rCBF over time (p ≤ 0.001). Significant effects for each contrast were based on the magnitude (Z = 3.09; p ≤ 0.001) and spatial extent (> 100 mm 3 ) of activation. All contrasts were adjusted for baseline age at Year 1.…”
Section: Discussionmentioning
confidence: 99%
“…Os indivíduos LHD tendem a responder aos estímulos rá-pida e impulsivamente, aumentando seu percentual de erros em tarefas neuropsicológicas. Dentre as tarefas que avaliam componentes das funções executivas, a fl uência verbal apresenta-se geralmente alterada em indivíduos LHD, após lesões corticais ou talâmicas (Annoni et al, 2003). Quanto às habilidades de planejamento e resolução de problemas, Colvin, Dunbar e Grafman (2001) constataram que pacientes LHD foram signifi cativamente piores em tarefas que avaliam essas funções quando comparados aos controles, mas melhores quando a base de comparação era pacientes LHE e lesados bilaterais.…”
Section: Alterações Cognitivasunclassified